Money for Nothing: The Impact of Compensation on Customers’ Bad-Mouthing in Service Recovery Encounters - Arsenovic, Jasenko; Edvardsson, Bo; Otterbring, Tobias; Tronvoll, Bård (Marketing letters, 2023)
As one of the retailer’s most potent recovery tactics to offset disgruntled customers, firms invest heavily in compensation to increase customer satisfaction and improve loyalty. However, the effectiveness of this tactic remains unclear. This study examines whether firm-offered compensation affects customers’ emotional responses and bad-mouthing behavior (i.e., telling others about a particular problem). Importantly, the study investigates whether the level of collaboration during the recovery encounter moderates the link between compensation and customers’ emotional responses, and whether collaborative efforts influence the effectiveness of compensation. The findings indicate that collaboration during the recovery encounter is necessary if compensation is to mitigate negative emotional responses, with downstream effects on bad-mouthing behavior. In confirming the importance of collaboration during recovery encounters, the findings have critical managerial and financial implications.